COMMUNITY BASED SOCIAL MARKETING DALAM PROGRAM PENGGALAKAN IBU-IBU SADAR ASI - Adrianto, Rifandy (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
Mother's Milk (ASI) is the best food for babies up to 6 months of age because it containsa variety of nutrients that are needed by the baby to grow and develop optimally. Variousstudies have shown the benefits of breastfeeding for both mother and baby, includingprotection against the risk of infection in infants, to optimize the cognitive developmentof children, as well as reduce the risk of breast cancer and ovarian cancer. Socialmarketing uses the concepts of market segmentation , consumer research , developmentand testing product concepts , communication is directed , provision of facilities ,incentives and changes in theory to maximize the response of the target group. Socialmarketing involves the promotion of breastfeeding What do Operates Aggressive PostedAssociation of Breastfeeding Mothers Indonesia . AIMI ( Indonesian BreastfeedingAssociation ) is a non-profit organization and non-profit TO commercial interests and